Clinical activity of a new regimen combining gemcitabine and alemtuzumab in high‐risk relapsed/refractory chronic lymphocytic leukemia patients. (17th September 2014) - Oberic, Lucie; Vaillant, Willy; Hebraud, Benjamin; Recher, Christian; Suc, Etienne; Houyau, Philippe; Laurent, Guy; Ysebaert, Loic
Abstract Optimal treatment strategies are lacking in relapsed/refractory (R/R) chronic lymphocytic leukemia (CLL). Gemcitabine has shown activity and acceptable safety profile in B‐cell lymphomas. We present a retrospective case review of gemcitabine and alemtuzumab, every 21 d (for up to six courses) in 27 community‐based patients with high‐risk R/R CLL. Median age was 70 yr (44–83 yr), 55% patients had Binet stage C, deletion 17p (del(17p)) and/or deletion 11q (del(11q)) were found in 65% and 27%, bulky disease in 55.5%, and fludarabine‐refractoriness in 48% of cases, respectively. Overall response rate was 63% (29.6% clinical CR and 33.4% PR). At a median follow‐up of 31 months, median PFS and OS were 15.4 and 24 months. In multivariate analysis, median OS is influenced by prior lines of treatment = 3 and bulky disease. Combination of alemtuzumab and gemcitabine appears to be an active, easy to administrate treatment in routine practice, high‐risk R/R CLL patients.